2007
DOI: 10.1242/dev.02800
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilafollicle cells are patterned by multiple levels of Notch signaling and antagonism between the Notch and JAK/STAT pathways

Abstract: The specification of polar, main-body and stalk follicle cells in the germarium of the Drosophila ovary plays a key role in the formation of the egg chamber and polarisation of its anterior-posterior axis. High levels of Notch pathway activation, resulting from a germline Delta ligand signal, induce polar cells. Here we show that low Notch activation levels, originating from Delta expressed in the polar follicle cells, are required for stalk formation. The metalloprotease Kuzbanian-like, which cleaves and inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
130
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 46 publications
(50 reference statements)
12
130
0
1
Order By: Relevance
“…[37][38][39][40] Furthermore, previous reports showed that Notch expression in mouse embryonic dental mesenchyme is upregulated by retinoic acid, a specific inducer of MK transcription. 10,11 In addition, Jak2 was found to modulate cell-cell adhesion in epithelial cells and EMT, which occurs during malignant development.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[37][38][39][40] Furthermore, previous reports showed that Notch expression in mouse embryonic dental mesenchyme is upregulated by retinoic acid, a specific inducer of MK transcription. 10,11 In addition, Jak2 was found to modulate cell-cell adhesion in epithelial cells and EMT, which occurs during malignant development.…”
Section: Discussionmentioning
confidence: 98%
“…24,59 Therefore, we suggest that the MK-Notch2-Stat3 pathway contributes to EMT, which is one of the important component of neonatal and tumor development. [5][6][7][8][9][10]31,[37][38][39][40][60][61][62][63] Since EMT plays a specific role in the migration of cells from a primary tumor into the circulation [1][2][3][4] an improved understanding of the role of MK-Notch2-Stat3 signaling in the EMT may provide a rationale for developing additional targeted cancer therapies. incubated with yeast extracts (100 μg) expressing the pGal4-ADNotch2 fusions tagged with HA-epitope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specification of these polar cells depends on a relay of Notch and JAK/STAT signaling between subsequent germ line cysts as they bud out of the germarium. 23,24 Drosophila Pur-α is part of mRNP transport complexes. Our results indicate that Pur-α may participate in the transport of mRNAs into the growing oocyte.…”
Section: Introductionmentioning
confidence: 99%
“…2A). In addition, the expression of two other Notch reporters, Gbe-lacZ (Furriols and Bray, 2001) and m7-lacZ (Assa-Kunik et al, 2007), remained unchanged in follicle cells with miR-7 overexpression (data not shown), indicating that miR-7 does not regulate Notch activity [NICD/Su(H) mediated activation] in follicle cells. In addition to Notch, our previous findings have demonstrated that the EcR pathway also regulates the E/A switch (Sun et al, 2008).…”
Section: Research Articlementioning
confidence: 96%